Determinan yang berpengaruh terhadap perawatan ortodontik pada remaja di Kota Denpasar - Ni Made Putri Meiliawati; Nyoman Desak Ari Susanti; Desak Putu Yuli Kurniati (School of Dentistry Faculty of Medicine Udayana University, 2019)
Introduction: Adolescents in the aged of 10 to 24 years in Denpasar ranked highest in orthodontic treatment for about 3.6%. Adolescents behaviour in orthodontic treatment is very important, because especially the use of fixed orthodontic appliance could have an impact in increase amount of plaque that can cause dental caries, as a result of the difficulty of oral hygiene procedures on patients. The purpose of this study is to determine adolescent behaviour in orthodontic treatment. Method: This study used a cross-sectional analytic design. Sampling technique used is purposive sampling with total sample 66 and respondent were taken with an age range of 12-25 years who are on fixed orthodontic treatment in Denpasar. Data were collected using questionnairies to determine the behavior of adolescents to fixed orthodontic treatment. Result: The results showed that the average respondents have good knowledge 40.9% with good behavior, good attitude 63.6% with good behavior, good cost 42.4% with good behavior, good source of information, less infrastructure 68.2% with less behavior, and good health care 60.6% with good behavior. Conclusion: Based on the results of research conducted that there is a relationship between infrastructure with orthodontic treatment behavior, while other variables do not show the relationship of orthodontic treatment behavior, and the most influential aspect from fixed orthodontic treatment are infrastructure.